Sociolinguistic Impact of Borrowings: Challenges and Methods of Translation - qizi, Olimjonova Fazilat Rustam (Journal of Innovation in Education and Social Research, 2025)
The article is devoted to the study of linguistic borrowings, their classification, historical background, causes, and the difficulties they present in the process of translation. It regards the significance of borrowings in language development and highlights the sociolinguistic factors. Special attention is paid to the types of borrowings, such as lexical, semantic, morphological, and syntactic, as well as to the strategies translators use to handle foreign elements in target languages. This article draws on various scholarly sources and provides illustrative examples to support theoretical observations.